2020
DOI: 10.1093/ons/opaa096
|View full text |Cite
|
Sign up to set email alerts
|

Access-Site Complications in Transfemoral Neuroendovascular Procedures: A Systematic Review of Incidence Rates and Management Strategies

Abstract: BACKGROUND The femoral artery is the most common access route for cerebral angiography and neurointerventional procedures. Complications of the transfemoral approach include groin hemorrhages and hematomas, retroperitoneal hematomas, pseudoaneurysms, arteriovenous fistulas, peripheral artery occlusions, femoral nerve injuries, and access-site infections. Incidence rates vary among different randomized and nonrandomized trials, and the literature lacks a comprehensive review of this subject. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
0
33
2
Order By: Relevance
“…However, the incidence of major complications (2.51%) in our cohort was greater than those previously reported by Oneissi et al for these three groups (0.92%, 0.21%, and 0.83%, respectively). 14 On the other hand, rates of groin pseudoaneurysm and arterial dissection in patients from our cohort were 0.83% (4/479) and 1.04% (5/479), respectively, lower than those reported previously. A 2018 review of 8 RCTs reported groin/puncture site hematoma rates of 3.6%, a groin pseudoaneurysm rate of 1%, and an arterial dissection rate of 2%, 21 and a 2020 review of 7 prospective trials of EVT with transfemoral access reported a major access-site complication rate of 1.67% and a total complication rate of 4.59%.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…However, the incidence of major complications (2.51%) in our cohort was greater than those previously reported by Oneissi et al for these three groups (0.92%, 0.21%, and 0.83%, respectively). 14 On the other hand, rates of groin pseudoaneurysm and arterial dissection in patients from our cohort were 0.83% (4/479) and 1.04% (5/479), respectively, lower than those reported previously. A 2018 review of 8 RCTs reported groin/puncture site hematoma rates of 3.6%, a groin pseudoaneurysm rate of 1%, and an arterial dissection rate of 2%, 21 and a 2020 review of 7 prospective trials of EVT with transfemoral access reported a major access-site complication rate of 1.67% and a total complication rate of 4.59%.…”
Section: Discussioncontrasting
confidence: 81%
“…Disaggregated, access-site complications in our retrospective cohort treated with EVT using US-guided puncture (4.18%) were comparable with a 2020 systematic review of 16 randomized controlled trials (RCTs) and 17 observational studies, in which the incidence of complication with no US guidance was reported as 5.13% and 2.78%, respectively. 14 Furthermore, our incidence of minor complications (1.67%) was markedly lower than rates previously reported in RCTs (4.07%) and observational studies with or without VCDs (2.05% and 2.85%, respectively). However, the incidence of major complications (2.51%) in our cohort was greater than those previously reported by Oneissi et al for these three groups (0.92%, 0.21%, and 0.83%, respectively).…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations